PENERAPAN APLIKASI E-LEARNING MAPEL MATEMATIKA UNTUK KELAS I SD NEGERI SIDOREJO 01 DENGAN METODE MDLC - Setiadi, Teguh; Setiawan, Alif (Journal of Computer Science and Technology (JCS-TECH), 2024)
Conventional (traditional) learning tends to transfer the knowledge they have to students and students receive it passively and uncritically. This situation makes students use mathematical formulas without understanding where and how these formulas are formed. Students are often positioned as people who "don’t know anything" who just wait for what the teacher gives. This causes students to become passive and less motivated in participating in learning. Motivation is one of the factors that influence the learning process and outcomes, one of which is at SD Negeri Sidorejo 01, Gringsing District, in the learning process there are still many obstacles, especially for class I. In the teaching and learning process the teacher always provides input that can provide motivation to students to function as a motivator. , director and driver of behavior. The reality that occurs is that students only learn by applying a system of sitting, being quiet, listening and taking notes. One strategy to increase students’ learning motivation in learning mathematics is the application of learning media in the form of e-learning applications. Considering that young children are more interested in e-learning applications than just being given material and practice questions to note down. In this regard, by implementing the Demonstration Method, learning media as a medium for learning Mathematics will more easily attract children’s attention to learning, as well as make it easier for teachers to teach because the appearance of the media with animations is made simpler and more attractive.